A case of fulminant hepatitis cured with the glucagon-insulin treatment - KINOSHITA, Hiroshi; SUGA, Mitsuo; FUJISAWA, Yasunori; FUJISHIMA, Akira; SAITO, Michiko; ANZAI, Tetsuro; FUJITA, Hideo; HOSOKAWA, Yukio; YOKOYAMA, Yoko (Kanzo, 1980)
A 17-year-old male patient with fulminant hepatitis who could be cured with the glucagon-insulin (G-I) treatment is reported. The patient was severely jaundiced (total scrum bilirubin 12.6mg/dl), his serum alanine aminotransferase 828 units, blood ammonia 101μg/dl and both HBs antigen and HBs antibody were simultaneously detected with the radioimmunoassay. Intensive parenteral administrations of prednisolone and l-DOPA, combined with rectal applications of lactulose, proved ineffective in preventing from his Grade III (Adams and Foley) hepatic encephalopathy with asterexis. The G-I treatment was therefore started, which resulted in awakening from coma with a decrease of blood ammonia. During the clinical course, serum AFP level was as high as 782ng/ml, and the liver biopsy specimen obtained after recovery showed cirrhosis of the liver. The mechanism by which the G-I treatment favours the fulminant hepatic disorder was discussed.